2019
DOI: 10.3390/coatings9120789
|View full text |Cite
|
Sign up to set email alerts
|

Applying Baghdadite/PCL/Chitosan Nanocomposite Coating on AZ91 Magnesium Alloy to Improve Corrosion Behavior, Bioactivity, and Biodegradability

Abstract: Magnesium alloys have received a great amount of attention regarding being used in biomedical applications; however, they show high degradability, poor bioactivity, and biocompatibility. To improve these properties, surface modification and various types of coatings have been applied. In this study, an anodized AZ91 alloy was coated with a polymer matrix composite made of polycaprolactone/chitosan (PCL/Ch) with different percentages of baghdadite to improve its resistance to corrosion, bioactivity, and biocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 38 publications
(61 reference statements)
2
18
0
Order By: Relevance
“…By applying the polymer-ceramic coating, the corrosion rate further decreased, the amount of magnesium on the surface decreased, and a peak resulting from phosphorus appeared (Figure 2f), indicating the deposition of phosphate groups on the surface. The SEM images of the surfaces of modified and unmodified samples coated with different composites were shown in our previous study [28]. The MgO layer and forsterite particles on the surface of AZ91 alloy play a protective role, improving the bioactivity of alloy, and can act as an intermediate layer for better adhesion of the coating to the substrate.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…By applying the polymer-ceramic coating, the corrosion rate further decreased, the amount of magnesium on the surface decreased, and a peak resulting from phosphorus appeared (Figure 2f), indicating the deposition of phosphate groups on the surface. The SEM images of the surfaces of modified and unmodified samples coated with different composites were shown in our previous study [28]. The MgO layer and forsterite particles on the surface of AZ91 alloy play a protective role, improving the bioactivity of alloy, and can act as an intermediate layer for better adhesion of the coating to the substrate.…”
Section: Resultsmentioning
confidence: 79%
“…The MgO layer and forsterite particles on the surface of AZ91 alloy play a protective role, improving the bioactivity of alloy, and can act as an intermediate layer for better adhesion of the coating to the substrate. As shown in [28], a smooth and uniform layer on the surface of MAO was observed as a result of applying the PCL/chitosan polymer coating. An increase in the roughness of the specimens was observed as a result of adding different amounts of baghdadite powder.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The results demonstrated that the nanocomposite coating was able to act as an excellent passivation layer to prevention diffusion and corrosion so that the corrosion current decreased significantly and the charge transfer resistance increased noticeably. Soleymani et al [150] incorporated different amounts of baghdadite mineral to polycaprolactone (PCL)/chitosan (Ch) for improving the resistance to corrosion, biocompatibility, as well as bioactivity of the anodized AZ91 alloy. According to the results, the nanocomposite coating containing 3 wt % baghdadite showed hydrophobic behavior that led to decreasing the corrosion current density for the magnesium alloy and the enhancement of its corrosion resistance.…”
Section: Polymeric Nanocomposite Coatingsmentioning
confidence: 99%